The Correlation between Sleep Quality and Working Memory Capacity on Student of Senior High School - Ardian Pratiaksa; Nanang Wiyono; Sinu Andhi Jusup (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background: Sleep is an active, repetitive and reversible behaviour serving several different function, one of it is the function to develop memory s abbility. Lack of sleep is one of big problem faced by the modern society nowadays. In the big city like Jakarta, most of the adolescents have sleep disorder. This research intents to prove correlation between sleep quality and working memory capacity on student of Senior High School. Methods: This research was a cross-sectional analytic observational. The population sample was students in the 10th grade of 4 Surakarta Senior High School. By using purposive sampling method, the total restricted samples were 66 students. The instruments were Pittsburgh Sleep Quality Index, which is used to check the sleep quality scores, and Reading Span Test, to check the working memory capacity. Data was analyzed by Spearman Correlation test. Results: The respondents were 66 students, 33 students (50%) with bad sleep quality, 33 (50%) others were students with good sleep quality. The result showed high positive and significant correlation between sleep quality and working memory capacity (r = 0.814 and P = 0.000). Conclusions: There is high positive and significant statistic correlation between sleep quality and working memory capacity on students of senior high school. Keywords: Senior high school students, sleep quality, working memory capacity.